Pelatihan Aplikasi Perkantoran Bagi Masyarakat Kelurahan Sidorejo - Ali Akbar Ritonga, Sahat Parulian Sitorus, Budianto Bangun, Rahmadani Pane (PT.JNDI, JURNAL BIMA, 2024)
A village is a community unit that has territorial boundaries and has the authority to manage all the interests of residents or local communities. Villages are led by the Village Head who is assisted by village officials and supervised by the Village Consultative Body in accordance with Minister of Home Affairs Regulation number 110/2016 concerning the duties and functions of the BPD. The lack of knowledge of citizens regarding Information Technology such as the operation of Microsoft Word and Excel in terms of writing correspondence is an obstacle in their activities, especially for high school/vocational level students or office workers. The aim of this Microsoft Word and Microsoft Excel training is to improve the quality of Human Resources ( HR) for the people of Sidorejo village, Labuhanbatu Regency. The methods in this training are the discussion method and the practice method. The results of this training show that there has been an increase in the skills of the residents of Sidorejo village, Labuhanbatu district in operating and using Microsoft Word and Microsoft Excel, this can help streamline daily work and increase residents' knowledge about science and technology.